Sensory Science Project Learning Methods for Student Readiness to Enter Elementary School - Ratna Prayudiptya Azarine; Nur Ainy Fardana; Dewi Retno Suminar (Program Studi Psikologi, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2024)
Researchers designed the sensory science project (SSP) learning model according to the cognitive and psychological development of early childhood. SSP contains sensory stimulation activities and knowledge material which are arranged in an integrated manner in an activity project. This research aims to determine the effect of the SSP learning method on students' readiness to enter elementary school.This research method is quantitative research analysis with a quasi experiment approach. This research design uses a nonequivalent comparison group, conducting a pre-test and post-test on the control group and experimental group at the same time (Creswell, 2016). The data collected used the Nijmeegse schoolbekwaamheids Test (NST) and subject observation. The learning intervention used uses the sensory science project (SSP) module which has gone through a module testing process. The research subjects were 24 children, aged 5-6 years who were attending early childhood education at TK B level at TK RJ Sidoarjo. The results of this research found that there was an influence of implementing the SSP model on children's readiness to enter elementary school. The independent sample t-test produced a value of t(19)=2.392, p=0.027. The average posttest score for the experimental group was 55.70, while for the control group it was 46.73. The average posttest score for the experimental group was higher than the control group. This proves that there was a greater increase in scores for the experimental group after being given the SSP learning intervention. The results of this research can be used as input and consideration in designing educational methods for early childhood which include inquiry learning, sensory integration and project based learning. It is hoped that this method can support children's school readiness to enter elementary school.Peneliti merancang model pembelajaran sensory science project (SSP) sesuai dengan perkembangan kognitif dan psikologis anak usia dini. SSP berisi kegiatan stimulasi sensori dan materi pengetahuan yang disusun secara terintegrasi dalam sebuah proyek kegiatan. Penelitian ini bertujuan untuk mengetahui pengaruh metode pembelajaran SSP terhadap kesiapan siswa memasuki SD. Metode penelitian ini adalah analisis penelitian kuantitatif dengan pendekatan quasi experiment. Desain penelitian ini menggunakan nonequivalent comparasion group, melakukan pre test dan post test kepada kelompok kontrol dan kelompok eksperimen di waktu yang bersamaan (Creswell, 2016). Penggalian data yang digunakan menggunakan Nijmeegse Schoolbekwaamheids Test (NST) dan observasi subyek. Intervensi pembelajaran yang digunakan menggunakan modul sensory science project (SSP) yang telah melalui proses uji coba modul. Subyek penelitian berjumlah 24 anak, usia 5-6 tahun yang sedang mengikuti pendidikan usia dini jenjang TK B di TK RJ Sidoarjo. Hasil penelitian ini menemukan adanya pengaruh penerapan model SSP terhadap kesiapan anak masuk SD. Uji independent sample t-test menghasilkan nilai t( 19)=2,392, p=0,027. Nilai rata-rata posttest untuk kelompok eksperimen adalah 55,70, sedangkan pada kelompok kontrol adalah 46,73. Rata-rata nilai posttest kelompok eksperimen lebih tinggi daripada kelompok kontrol. Hal ini membuktikan bahwa ada peningkatan nilai lebih besar terhadap kelompok eksperimen setelah diberi intervensi pembelajaran SSP. Hasil penelitian ini dapat digunakan sebagai bahan masukan dan bahan pertimbangan dalam merancang metode pendidikan untuk anak usia dini yang mencakup pembelajaran inquiry, sensori integrasi dan project based learning. Diharapkan metode tersebut dapat mendukung kesiapan sekolah anak untuk memasuki sekolah dasar.